Embracing The Future : Technology’s Role in Shaping the Future of Work for MEITD Officers - Lee, Jun Choi; Sopian, Bujang; Nadri Aetis Heromi, Basmawi; Syahrul Nizam, Junaini; Ahmad Sofian, Shminan (Unit Pengurusan dan Pembangunan Sumber Manusia, Jabatan Premier Sarawak, 2024)
In an era of rapid technological evolution, government sectors, including the Ministry of Education, Innovation, and Talent Development (MEITD) in Sarawak, are experiencing a significant transformation in the nature of work. This study aims to explore the role of emerging technologies, such as artificial intelligence (AI), automation, and data analytics, in reshaping the operations, decision-makingproces ses, and competencies required for MEITD officers. The research focuses on five key objectives: identifying the most impactful technological advancements; assessing the influence of digital tools on work processes; analysing the evolving skills and training programs needed for successful technology adoption; investigating the challenges faced in integrating new technologies; and forecasting future trends that will shape the ministry’s role within the broader educational landscape in Sarawak. By providing insights into the opportunities and barriers presented by technological advancements, this study contributes to strategic workforce development, aiming to foster a tech-savvy, adaptable, and future-ready MEITD. The findings will also offer recommendations for addressing digital literacy gaps, infrastructure issues, and fostering a culture of continuous learning to maximize the benefits of technology in the public sector.